ChemInform Abstract: Acid‐Mediated Ring‐Expansion Reaction of N‐Aryl‐2‐vinylazetidines: Synthesis and Unanticipated Reactivity of Tetrahydrobenzazocines. Issue 44 (4th November 2014) - Shimizu, Tomoaki; Koya, Shunsuke; Yamasaki, Ryu; Mutoh, Yuichiro; Azumaya, Isao; Katagiri, Kosuke; Saito, Shinichi
Abstract In the presence of 1.5 equivalents of H2SO4, vinylazetidines are found to undergo ring expansion to benzazocine derivatives like (II) which are unstable undergoing ring contraction to vinyltetrahydroquinolines (III) under slightly acidic conditions.